2003
DOI: 10.1002/pits.10134
|View full text |Cite
|
Sign up to set email alerts
|

Family‐centered positive psychology: Focusing on strengths to build student success

Abstract: University of Nebraska-LincolnFamily-centered positive psychology (FCPP) is defi ned as a framework for working with children and families that promotes strengths and capacity building within individuals and systems, rather than one focusing solely on the resolution of problems or remediation of defi ciencies. This approach to family-based services is predicated on the belief that child and family outcomes will be enhanced if members participate in identifying needs, establishing social supports and partnershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 13 publications
1
33
0
1
Order By: Relevance
“…The student's compliance increased significantly from baseline to treatment and generalization phases. In a paper describing CBC within a context of "family-centered" services, Sheridan, Warnes, Cowan, Schemm, and Clarke (2004) reported the use of CBC to decrease the duration of tantrums of a four-yearold male attending Early Childhood Special Education (ECSE). Behavioral data indicated that the goal was met quickly upon intervention implementation.…”
Section: Review Of Case Studiesmentioning
confidence: 99%
“…The student's compliance increased significantly from baseline to treatment and generalization phases. In a paper describing CBC within a context of "family-centered" services, Sheridan, Warnes, Cowan, Schemm, and Clarke (2004) reported the use of CBC to decrease the duration of tantrums of a four-yearold male attending Early Childhood Special Education (ECSE). Behavioral data indicated that the goal was met quickly upon intervention implementation.…”
Section: Review Of Case Studiesmentioning
confidence: 99%
“…Likewise, increasing personal effectiveness is aligned with constructs like self-determination (Ryan & Deci, 2000). Or again, enhancing the quality of relationships between people is central to many PPIs, such as family-centred positive psychology (Sheridan et al, 2004). Thus, already we can see it would not be too much of a leap for PP to incorporate ethical principles such as these.…”
Section: Learning From Counselling and Psychotherapymentioning
confidence: 99%
“…As such, intervention models that infuse and promote a partnership orientation may influence outcomes experienced as a function of that intervention. A partnership orientation is counter to one focusing on the sole identification of problems or remediation of deficiencies within the child or an isolated system (Sheridan, Warnes, Cowan, Schemm, & Clarke, 2004). A partnership approach originates from the assumption that "child and family outcomes will be enhanced if members participate in identifying needs, establishing social supports and partnerships, and acquiring new skills and competencies, rather than simply receiving services from professionals" (Sheridan et al, 2004, pp.…”
mentioning
confidence: 99%
“…Although general principles of "effective helping" are present in CBC (i.e., "the act of enabling individuals or groups to become better able to solve problems, meet needs, or achieve aspirations by promoting the acquisition of competencies"; (Dunst, Trivette, & Deal, 1994, p. 162), families and teachers who participate in CBC have been found to hold different perspectives on what effective helping entails (Sheridan et al, 2004). Consequently, it is important to understand each perspective in the helping process (Sheridan et al, 2004).…”
mentioning
confidence: 99%